2023
DOI: 10.1186/s12888-023-04775-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of probable mental, neurological and substance use conditions and case detection at primary healthcare facilities across three districts in Ghana: findings from a cross-sectional health facility survey

Abstract: Background Few studies have examined the prevalence of mental, neurological and substance use (MNS) conditions, case detection and treatment in primary healthcare in rural settings in Africa. We assessed prevalence and case detection at primary healthcare facilities in low-resource rural settings in Ghana. Methods A cross-sectional survey was conducted at the health facility level in three demonstration districts situated in Bongo (Upper East Regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…This is consistent with findings from a study by Ae-Ngibise and others, 2023 who found a low detection rate of people with MNS conditions in routine primary healthcare facilities. Up to 98% of MNS conditions were not detected [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with findings from a study by Ae-Ngibise and others, 2023 who found a low detection rate of people with MNS conditions in routine primary healthcare facilities. Up to 98% of MNS conditions were not detected [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those who would have benefited from the services at the lower public health facilities may also have poor health seeking behaviour. As hypothesized above for mental disorders, a lack of knowledge and skills in the management of substance use disorders among primary health care workers could also be a factor in under/misdiagnosis of these health conditions [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation